Supporting research in area studies a guide for academic libraries - Pitman, Lesley (Chandos information professional series, 2015)
Supporting Research in Area Studies: A Guide for Academic Libraries focuses on the study of other countries or regions of the world, crossing traditional disciplinary boundaries in the humanities and social sciences. The book provides a comprehensive guide for academic libraries supporting communities of researchers, exploring the specialist requirements of these researchers in information resources, resource discovery tools, information skills, and the challenges of working with materials in multiple languages. The book makes the case that adapting systems and procedures to meet these needs will help academic libraries be better placed to support their institutions' international agenda. Early chapters cover the academic landscape, its history, area studies, librarianship, and acquisitions. Subsequent chapters discuss collections management, digital products, and the digital humanities, and their role in academic projects, with final sections exploring information skills and the various disciplinary skills that facilitate the needs of researchers during their careers